Information Environment, Dividend Changes, and Signaling: Evidence from ADR Firms* - AGGARWAL, RAJ; CAO, JIAN; CHEN, FENG (Contemporary Accounting Research, 2012)
This is an accepted manuscript of an article published by Wiley.